2011
DOI: 10.1016/j.yjmcc.2010.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Loss of interstitial collagen causes structural and functional alterations of cardiomyocyte subsarcolemmal mitochondria in acute volume overload

Abstract: Volume overload (VO) caused by aortocaval fistula (ACF) is associated with oxidative/inflammatory stress. The resulting inflammation, matrix metalloproteinase (MMP) activation, and collagen degradation is thought to play a pivotal role in left ventricular (LV) dilatation and failure. Since mitochondria are also targets for inflammation and oxidative stress, we hypothesized that there would be bioenergetic dysfunction with acute VO. In Sprague-Dawley rats subjected to 24 hrs of ACF, there was a two-fold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 39 publications
(46 reference statements)
4
61
0
Order By: Relevance
“…5, A and B), suggesting that this could be a possible mechanism of increased mitochondrial Ca 2ϩ uptake (29,39), and this effect was not blunted by the addition of allopurinol to the ACF group. Since XO has been shown to be increased in VO, we decided to determine if the protein levels of MnSOD were altered as a compensatory mechanism to cope with increased levels of ROS, specifically O 2 ·Ϫ .…”
Section: Pressure-volume Analysismentioning
confidence: 91%
See 3 more Smart Citations
“…5, A and B), suggesting that this could be a possible mechanism of increased mitochondrial Ca 2ϩ uptake (29,39), and this effect was not blunted by the addition of allopurinol to the ACF group. Since XO has been shown to be increased in VO, we decided to determine if the protein levels of MnSOD were altered as a compensatory mechanism to cope with increased levels of ROS, specifically O 2 ·Ϫ .…”
Section: Pressure-volume Analysismentioning
confidence: 91%
“…Sprague-Dawley rats (200 -250g) at 12 wk of age were subjected to either to sham or ACF, as previously described by our laboratory (18,33,39,40), with and without the XO inhibitor allopurinol (100 mg/kg, Sigma) for 8 wk. Allopurinol was started at the time of surgery and delivered in standard rat chow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Volume overload is associated with a distinct profile of changes in the composition of the ECM that ultimately lead to chamber dilation and contribute to systolic dysfunction. In contrast to the marked accentuation in collagen deposition triggered by a pressure load, volume overload is associated with a reduction in interstitial collagen content due to increased MMP expression (113)(114)(115) and augmented autophagic degradation of procollagen in cardiac fibroblasts (116). Pharmacologic inhibition studies suggested that MMP activation is directly implicated in dilative remodeling of the volume-overloaded ventricle (117), but the mechanisms responsible for the distinct cell biological changes and matrix alterations in volume overload remain poorly understood.…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%